TROP‐2 expression in papillary thyroid carcinoma: Potential Diagnostic Utility. Issue 1 (19th October 2015) - Simms, Anthony; Jacob, Reuben P.; Cohen, Cynthia; Siddiqui, Momin T.
Abstract : TROP‐2 is a type I transmembrane glycoprotein which is over‐expressed in various malignancies, and is related to epithelial cell adhesion molecule (EpCAM), also called TROP‐1, gp40, and KSA. In this study, we evaluated TROP‐2 expression in papillary thyroid carcinoma (PTC) and compared it to other thyroid neoplastic and non‐neoplastic lesions. Immunohistochemical (IHC) evaluation for TROP‐2 was performed on 137 thyroid fine needle aspiration (FNA) cell blocks (CB) which included classic PTC (64), follicular variant PTC (FVPTC) (10), anaplastic thyroid carcinoma (AC) (2), medullary carcinoma (MC) (8), follicular neoplasms (FN) (8), Hurthle cell neoplasms (HCN) (9), follicular lesion of uncertain significance (FLUS) (12), and benign thyroid nodule (BTN) (24). IHC for TROP‐2 expression was also performed on 331 BTN and malignant tumor tissue sections in tissue microarray (TMA). Membranous staining in >5% of tumor cells was considered positive. TROP‐2 stained 61 of 64 PTC CB, 7 of 10 FVPTC CB, and 9 of 12 FLUS CB. All other cases were negative for TROP‐2. TROP‐2 showed a sensitivity of 95.31% and specificity of 89% for classic PTC in FNA CB. In TMA samples, TROP‐2 stained 54 of 60 classic PTC cases and hence showed a high sensitivity and specificity. All BTN in CB and TMA were negative. We conclude that TROP‐2 is a highly sensitive and specific IHC marker for identifying classic PTC. TROP‐2 may play an important role in diagnosing classic PTC, especially in equivocal cases. This study also identifies a strong role for TROP‐2 in separating PTC from BTN. Diagn. Cytopathol. 2016;44:26–31. © 2015 Wiley Periodicals, Inc.